2001
DOI: 10.1002/1521-3773(20010518)40:10<1898::aid-anie1898>3.0.co;2-k
|View full text |Cite
|
Sign up to set email alerts
|

Noncoordinating Dendrimer Polyanions: Cocatalysts for the Metallocene-Catalyzed Olefin Polymerization

Abstract: A new class of noncoordinating anions are the carbosilane dendrimers with perfluoroarylborate end groups (see picture). They activate and stabilize metallocenes to give catalytic systems that polymerize olefins, such as ethene, propene, and 1‐hexene, with high activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(20 citation statements)
references
References 59 publications
0
20
0
Order By: Relevance
“…For instance, Mager et al reported a series of weakly coordinating carbosilane dendrimers with organoborate functionalities at the periphery. 39 The negatively charged dendrimers were used as cocatalysts for metallocene-catalyzed olefin polymerization. Ethene, propene, as well as ethene/propene and ethene/1-hexene mixtures were successfully polymerized.…”
Section: Organoborate-containing Polymersmentioning
confidence: 99%
“…For instance, Mager et al reported a series of weakly coordinating carbosilane dendrimers with organoborate functionalities at the periphery. 39 The negatively charged dendrimers were used as cocatalysts for metallocene-catalyzed olefin polymerization. Ethene, propene, as well as ethene/propene and ethene/1-hexene mixtures were successfully polymerized.…”
Section: Organoborate-containing Polymersmentioning
confidence: 99%
“…[54] The active form of the catalyst is cationic and is typically generated by a cocatalyst. [55] Co-catalysts G0 to G2 were synthesized with 4, 12, and 36 alkyl-tris-(pentafluorophenyl)borates at the periphery ( Figure 7). The interaction between the ion pair affects the overall activity, steroregularity, chain transfer, termination rate and lifetime of the metallocene catalyst.…”
Section: Peripherally Modified Dendrimers In Catalysismentioning
confidence: 99%
“…35). 80 In a series of reports, Jakle and co-workers have reported a new route to organoboron polymers of PS that contained well-defined boron-containing Lewis acids. 81 These acidic polymers have the potential for use as cocatalysts in olefin polymerization and as catalysts in organic syntheses.…”
Section: Figure 31mentioning
confidence: 99%